Design and Development of a Web Application for Outpatient Service Management at Sagaranten Community Health Center, Sukabumi Regency - Ermawati, Helmi; Yunengsih, Yuyun; Abdussalaam, Falaah (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2025)
This study aims to design a web-based outpatient service information system. The development of this system applies the waterfall method, with Data Flow Diagrams (DFD) used as modeling tools. Based on the findings, outpatient services at the Primary Healthcare Facility are still conducted manually. Patient data is stored using paper-based media, which leads to time-consuming data retrieval processes, as staff must search through paper sheets across multiple books and archives. Moreover, each entity is not yet integrated, resulting in slow, inaccurate, and irrelevant information output. To address these issues, an information system is needed to facilitate efficient data entry, collection, processing, searching, and reporting of patient data. The proposed information system is expected to reduce the existing problems in Primary Healthcare Facilities. With integrated media for data storage, patient data processing, and medical record files, registration officers can serve patients more quickly and easily during their visits for medical treatment.